2006
DOI: 10.1111/j.1399-3038.2005.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of fish, butter and margarine during pregnancy and development of allergic sensitizations in the offspring: role of maternal atopy

Abstract: It has been suggested that changes in dietary habits, particularly increased consumption of omega-6 polyunsaturated fatty acids (PUFA) and decreased consumption of omega-3 PUFAs may explain the increase in atopic disease seen in recent years. Furthermore, it seems possible that it is mainly prenatal or very early life environmental factors that influence the development of allergic diseases. It has also been suggested that intrauterine risk factors may act differently if mother themselves suffer from allergic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 30 publications
6
91
1
Order By: Relevance
“…These observations are in contrast to results from previous studies, which mainly, but not consistent, suggest that maternal fish intake during pregnancy protects against the development of childhood asthma and atopy. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Observational studies in large cohorts observed lower incidence of eczema in offspring of mothers with the highest fish consumption during pregnancy, 19,21 but not lower incidences of wheezing or asthma. In the Netherlands, fish consumption is relatively low, which can explain the differences in the observations.…”
Section: Maternal Fish Consumption and Atopic Symptoms Etm Leermakersmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are in contrast to results from previous studies, which mainly, but not consistent, suggest that maternal fish intake during pregnancy protects against the development of childhood asthma and atopy. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Observational studies in large cohorts observed lower incidence of eczema in offspring of mothers with the highest fish consumption during pregnancy, 19,21 but not lower incidences of wheezing or asthma. In the Netherlands, fish consumption is relatively low, which can explain the differences in the observations.…”
Section: Maternal Fish Consumption and Atopic Symptoms Etm Leermakersmentioning
confidence: 99%
“…7 Many observational and interventional studies, explored the associations of maternal fish consumption or fish oil supplementation during pregnancy with the risks of childhood asthma and atopy. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Although these studies showed a protective effect on at least one outcome, they were not all able to adjust for potential confounders. Also, previous intervention studies differed in selection of participants, types of intervention and definition of outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…Umbilical cord blood lipids from neonates who go on to develop atopy in early childhood appear to contain lower than normal amounts of EPA and DHA (see Sala-Vila et al (37) ). All five studies investigating the effect of maternal fish intake during pregnancy on atopic or allergic outcomes in infants/ children of those pregnancies concluded protective associations (46)(47)(48)(49)(50) . The protective effect varied between 25 and 95%, which might be attributed to differences in study design, exposure and outcome measure classification and assessment.…”
Section: N-3 Pufa Eicosanoids and Inflammatory Processesmentioning
confidence: 99%
“…Calvani et al [49] investigated associations between the type of fat in the maternal diet during pregnancy and allergic sensitization in five year old children born to allergic and non-allergic mothers. They reported less sensitization to common food allergens at 5 years of age with more frequent intake of fish during pregnancy in non-atopic mothers but not in the offspring of atopic mothers.…”
Section: At 5 Yearsmentioning
confidence: 99%